2021
DOI: 10.1093/icvts/ivab195
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous extracorporeal membrane oxygenation during high-risk airway interventions

Abstract: OBJECTIVES Practice patterns for the use of extracorporeal membrane oxygenation (ECMO) during high-risk airway interventions vary, and data are limited. We aim to characterize our recent experience using ECMO for procedural support during whole-lung lavage (WLL) and high-risk bronchoscopy for central airway obstruction (CAO). METHODS We performed a retrospective cohort study of adults who received ECMO during WLL and high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In recent years, the stent placement as an interventional treatment to palliate the critical airway obstruction caused by tumor is becoming widely accepted [7,8,[10][11][12]. Because stent placement is safe, minimally invasive, well tolerated, and is increasingly used in various benign and malignant conditions characterized by central airway stenosis [13,14,26,28]. However, stent placement also have defects, for example, it can increase the risk of major bleeding or complete bilateral obstruction of the main bronchus [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the stent placement as an interventional treatment to palliate the critical airway obstruction caused by tumor is becoming widely accepted [7,8,[10][11][12]. Because stent placement is safe, minimally invasive, well tolerated, and is increasingly used in various benign and malignant conditions characterized by central airway stenosis [13,14,26,28]. However, stent placement also have defects, for example, it can increase the risk of major bleeding or complete bilateral obstruction of the main bronchus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Immediately, we used early ECMO to manage di cult airway and support surgical procedure in ED. Previous clinical studies presented that use ECMO to ensure adequate ventilatory function (CO 2 removal and oxygenation) in stent placement and bronchoscopy for patients with critical airway obstruction [13,14,28]. Their starting time of ECMO was intraoperative, and mainly solved the problem of intraoperative hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, VV ECMO, cannulation site from femoral vein to internal jugular vein (or subclavian vein), was preferred for respiratory failure in thoracic surgeries. Previous studies have shown that VV ECMO can help to ensure adequate ventilatory function (CO 2 removal and oxygenation) when performing stent placement in patients with central airway obstruction [13,14,28]. VV ECMO can provide time to plan and implement adequate treatment, thereby minimizing procedure-related complications [28].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ECMO is deployed electively to mitigate the risk and ensure the safe and successful performance of high-risk procedures in at-risk patients. Elective initiation of ECMO has been associated with better outcomes than emergent rescue placement in the setting of cardiopulmonary arrest [4]. Further, by anticipating operative risks, a multidisciplinary team can decide on and prepare the most appropriate ECMO modality to provide support if needed.…”
Section: Introductionmentioning
confidence: 99%